The Supreme Court of Canada and its justices, 1875-2000 : a commemorative book = La Cour suprême du Canada et ses juges, 1875-2000 : un livre commémoratif. (Published by Dundurn Group and the Supreme Court of Canada in Cooperation with Public Works and Government Services Canada, 2000)
A commemoration of two significant dates, The Supreme Court of Canada and its Justices is also a colourful portrait and an indispensable reference book. A bilingual co-publication of Dundurn Press and the Supreme Court of Canada, the book contains biographies, with portraits or photographs, of every Justice appointed to the Court since its inception. The Supreme Court of Canada and its Justices also features a preface by Chief Justice Beverley McLachlin and a history of the Court by former Chief Justice Antonio Lamer. A succession list and a selected bibliography are included for res.